I Dont Want to Die Before Visiting Graceland: A Collaborative Autoethnography - Martínez, Alejandra (2014)
In this article, we use collaborative autoethnography to reflect on the different perceptions that can exist about the same event. We narrate our shared experience during a violent episode in which issues of race, class, and inequality of opportunities were present, involving not only our minds but also our bodies and emotions. We reflect on the impossibility to remain objective and neutral when observing reality.